2021
DOI: 10.1186/s13045-021-01073-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on diagnosis, stage, and initial treatment of breast cancer in the Netherlands: a population-based study

Abstract: Background The onset of the COVID-19 pandemic forced the Dutch national screening program to a halt and increased the burden on health care services, necessitating the introduction of specific breast cancer treatment recommendations from week 12 of 2020. We aimed to investigate the impact of COVID-19 on the diagnosis, stage and initial treatment of breast cancer. Methods Women included in the Netherlands Cancer Registry and diagnosed during four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
107
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(119 citation statements)
references
References 12 publications
7
107
0
5
Order By: Relevance
“…However, the incidence of stage IV tumors did not decline. As the incidence reduction mainly occurred for the lowest stage disease, the authors suggested that the delay in diagnosis would not have had a large impact on long-term outcomes (20). A multicentric analysis from Italy, reporting the effects in the first three months after lockdown, showed a significant difference in waiting times, proportion of patients with lymph-node involvement, and cancer grading, compared with the similar period from the previous year.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of stage IV tumors did not decline. As the incidence reduction mainly occurred for the lowest stage disease, the authors suggested that the delay in diagnosis would not have had a large impact on long-term outcomes (20). A multicentric analysis from Italy, reporting the effects in the first three months after lockdown, showed a significant difference in waiting times, proportion of patients with lymph-node involvement, and cancer grading, compared with the similar period from the previous year.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works addressed the impact of the COVID-19 pandemic on regional or national settings [5, 50], on specific cancers [5,6,169], specific stages of the care pathway [54], or treatment modalities [22]. This scoping review provides a summary of cancer care performance indicators, concerning various diseases, from early detection to the treatment phase of the care pathway, within OECD countries.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has widely affected cancer care delivery. Substantial declines in the number of cancer diagnoses have been reported in the Netherlands [5, 6], Spain [7], Belgium [8], and Denmark [9]. While trying to minimize the risk of COVID-19 disease in cancer patients, changes in practice were pursued by oncologists, according to each setting’s capacity and recommendations released by oncology societies [1012].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, Eijkelboom and colleagues observed a decrease in breast cancer incidences across all age groups during the first month of the COVID-19 pandemic in the Netherlands [ 4 ]. In addition to the halt of the Dutch national breast cancer screening program, the increased reluctance of patients to visit their general practitioner along with the advice to vulnerable individuals to stay at home in the first month of the pandemic might have contributed to this decrease in breast cancer incidence during the pandemic [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, the incidence of breast cancer diagnoses fell with approximately 35% during the first months of the COVID-19 pandemic [ 5 , 6 ]. Moreover, one in three patients reported changes in their cancer care and increased concerns about the consequences of the delay in treatment and perceived barriers in access to health care were observed [ 3 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%